A journey to Darfur - Nostalgia Network, Inc.; AmericanLife TV Network (Firm); Not On Our Watch (Organization) ([S.l.] : Nostalgia Network, 2007)
"In April 2006 veteran journalist Nick Clooney was asked by his son, George, to accompany him to the troubled region of Darfur. The goal was to shine a light on the modern day genocide occurring in this remote and desolate region of Africa. They went unannounced; without press, without escort and without security, just Nick, George and cameraman, Mike Herron, a personal friend. This documentary is an account of their journey, the stories of unimaginable violence that have befallen the Darfurians and the courage of the aid workers who struggle to provide relief to two hundred thousand refugees. The documentary also provides background on the crises and the efforts of individuals and groups to stand up and say, "Not on our watch!"
DVD.
"100% of AmericanLife TV's proceeds on the sale of thisDVD go to www.notonourwatchproject.org. NOOW was created by George Clooney, Brad Pitt, Matt Damon, Don Cheadle and Jerry Weintraub to support existing humanitarian relief effortsand to ensure the protection of civilians in Darfur."--Container.
Keywords: Genocide -- Sudan -- Darfur; Humanitarian assistance -- Darfur (Sudan); International relief -- Darfur (Sudan); Darfur (Sudan); Documentary films